Investigation on Influence Factors of Photo-Induced PLZT-Based Ion Drag Pump - Xinjie Wang; Zhen Lv; Yuming Shao; Yujie Shi; Yao Yao; Jiong Wang (Micromachines)
The ion drag pump, as one kind of electrohydrodynamic pump, has received considerable attention in fluid applications due to its excellent pumping flow rate and pressure. However, there is a lack of systematic research about the factors that influence pumping performance of the ion drag pump. Here, a photo-induced ion drag pump based on the PLZT ceramic is proposed by combining the photoelectric effect and field emission phenomenon. The EHD model of this ion drag pump is constructed based on the mathematical model of the photovoltage of the PLZT ceramic, through which a series of finite element simulations are carried out to comprehensively investigate the factors that influence the pumping performance. The results demonstrate that such an ion drag pump is able to be improved by optimizing the electrode structure and fluid channel; increasing the light intensity; and providing a basic design guideline for applications of ion drag pumps in microfluidics, soft robots, and heat dissipation in micro devices.